Understanding Capital Accounting Practices by Laundry Entrepreneurs Based on Local Wisdom Values - Mohamad Anwar Thalib; Rafka Suaib; Nur Laila Lawani; Moh. Aldi (Studi Akuntansi, Keuangan, dan Manajemen, 2024)
Purpose: This study aims to understand capital accounting practices of laundry entrepreneurs based on local wisdom values. Methodology/Approach: This study uses an Islamic paradigm with an Islamic ethno-methodology approach. There are five data analysis stages: charity, knowledge, faith, revealed information, and ihsan. This study uses a qualitative method. There were two types of data collection: structured interviews and passive participant observations. Informants were selected using a type of informant determination in the form of purposive sampling. Results/findings: The research results show two capital accounting practices implemented by laundry entrepreneurs: the source of capital that comes from side business income, and the method of recording capital accounting in memory. These two capital accounting practices depend on the value of mutual help, which is reflected in establishing a laundry business to help the family economy. The elders often advise the value of helping each other in the household through the expression “delo tombowata lo tabu wawu labiya.” This expression contains the meaning of a peaceful household life. Limitations: The limitation of this study is that research informants who only gathered information from laundry owners did not include information sourced from customers of the laundry business. Contribution: This research presents the concept of accounting practices by laundry entrepreneurs based on local cultural values, namely mutual help between husbands and wives.